Cultural Lanscape of Bali Aga - Tenganan Traditional Village (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Tenganan Pegringsingan is one of the Balinese Aga or ancient traditional villages which is very unique and is expected to soon be included in the tentative list of world heritage lists to UNESCO. With this proposal, it is hoped that the number of tourists visiting will increase, so proper management is needed so that the negative impact does not damage the cultural landscape in the village. The purpose of this study is to identify the characteristics of the cultural landscape of the Balinese Traditional Village of Aga Tenganan Pegringsingan, and to analyze the potential and constraints that affect its sustainability. The method used is descriptive and spatial analysis. The results show that the potential that affects the sustainability of the cultural landscape is the tradition that is maintained. The spatial pattern is oriented towards spiritual and cosmological values ​​based on the beliefs and customary law of the community's traditions contained in awig-awig (Bali customary law). The spatial structure of the settlements and the surrounding landscape in the form of hills are formed based on the concept of Hindu cosmological philosophy of the Indra sect, utama-madya-nista concept, and the concept of macrocosm and microcosm balance. It is recommended that the management of the landscape conservation concept of the Bali Aga Tenganan Pegringsingan Traditional Village is a collaboration and integration of the concepts of natural resource conservation and the conservation of culture and traditions of indigenous peoples.